2013
DOI: 10.2478/v10015-012-0007-7
|View full text |Cite
|
Sign up to set email alerts
|

Immediate and Distracted Imitation in Second-Language Speech: Unreleased Plosives In English

Abstract: The paper investigates immediate and distracted imitation in second-language speech using unreleased plosives. Unreleased plosives are fairly frequently found in English sequences of two stops. Polish, on the other hand, is characterised by a significant rate of releases in such sequences. This cross-linguistic difference served as material to look into how and to what extent non-native properties of sounds can be produced in immediate and distracted imitation. Thirteen native speakers of Polish first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 62 publications
1
19
0
Order By: Relevance
“…Others investigated whether improvements following training in one modality transferred to the other modality and, if so, under what circumstances (Akahane-Yamada, McDermott, Adachi, Kawahara, & Pruitt, 1998; Bradlow, Akahane-Yamada, Pisoni, & Tohkura, 1999; Bradlow, Pisoni, Akahane-Yamada, & Tohkura, 1997; Hirata, 2004; Lopez-Soto & Kewley-Port, 2009; Thorin, Sadakata, Desain, & McQueen, 2018; Wong, 2013). Finally, imitation after a native speaker model has frequently been used as a window into the link between L2 perception and production (de Jong et al, 2009; Flege & Eefting, 1988; Hao & de Jong, 2016; Jia, Strange, Wu, Collado, & Guan, 2006; Rojczyk, 2013; Rojczyk, Porzuczek, & Bergier, 2013; Schouten, 1977). Imitation tasks are considered to be especially informative regarding this issue because they involve the engagement of the two systems in one task.…”
Section: Introductionmentioning
confidence: 99%
“…Others investigated whether improvements following training in one modality transferred to the other modality and, if so, under what circumstances (Akahane-Yamada, McDermott, Adachi, Kawahara, & Pruitt, 1998; Bradlow, Akahane-Yamada, Pisoni, & Tohkura, 1999; Bradlow, Pisoni, Akahane-Yamada, & Tohkura, 1997; Hirata, 2004; Lopez-Soto & Kewley-Port, 2009; Thorin, Sadakata, Desain, & McQueen, 2018; Wong, 2013). Finally, imitation after a native speaker model has frequently been used as a window into the link between L2 perception and production (de Jong et al, 2009; Flege & Eefting, 1988; Hao & de Jong, 2016; Jia, Strange, Wu, Collado, & Guan, 2006; Rojczyk, 2013; Rojczyk, Porzuczek, & Bergier, 2013; Schouten, 1977). Imitation tasks are considered to be especially informative regarding this issue because they involve the engagement of the two systems in one task.…”
Section: Introductionmentioning
confidence: 99%
“…The less than expected effect of memory load could be because when waiting for imitation in the long interval condition, participants rehearsed internally, which reduced the decay of phonetic details perceived from the stimuli, thus diminishing the difference between two memory load conditions. Studies that asked participants to do other tasks while waiting have reported stronger effect of memory load [7].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, they proposed that participants can operate on a phonetic mode of processing without any access to native phonology. In [7], native speakers of Polish imitated English unreleased plosives in two-stop sequences in two imitation conditions. In one condition, they imitated the stimuli immediately and, in another condition, they read a digit after the auditory input before imitating.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the acquisition of stop release suppression may be suggested to be an instrumental aspect of prosodic learning in L2 English. In the context of L1 Polish speakers learning English, previous studies by Bergier (2010) and Rojczyk et al (2013) have investigated the production of unreleased stops.…”
Section: Phonological and Phonetic Backgroundmentioning
confidence: 99%